First application of total skin electron beam therapy for Mycosis Fungoids in Iran - Banaee, Nooshin; Nedaie, Hassan Ali; Andalib, Bahram; Samei, Mahmood; hassani, hosein; Tizmaghz, Zohreh (JOURNAL OF ADVANCES IN PHYSICS, 2014)
Total skin electron beam therapy (TSEBT) is internationally considered as a treatment modality for cutaneous T-cell lymphoma for either curative purpose or palliative care. The first attempt to apply TSEBT in Iran took place at department of clinical oncology of Rock Center of Karaj. Irradiation was done by precise linear accelerator (ELEKTA) and was performed in the standing position of patient. To evaluate the treatment reliability and determination of physical characteristics of the clinical electron fields, specific measurements were done using thermoluminescent dosimeters. The results revealed that TSEBT can be routinely used by providing accurate dosimetric measurements to get homogenous dose coverage.